Thromboembolic risk factors and predictors of left atrial appendage thrombosis in Far North patients with nonvalvular atrial fibrillation - N. Yu. Khorkova; T. P. Gizatulina; A. V. Belokurova; E. A. Gorbatenko; E. I. Yaroslavskaya (Российский кардиологический журнал)
Aim. To analyze thromboembolic risk factors and identify additional predictors of left atrial appendage (LAA) thrombosis, which are not included in the CHA2DS2VASc scale, in long-term Far North residents with nonvalvular atrial fibrillation (AF).Material and methods. The study included 162 patients (men, 108; women, 54; mean age, 55,3±8,7 years) with non-valvular AF, living in the Far North, and 684 patients (men, 408; women, 276; mean age, 56,9±9,3 years), living in the temperate latitudes, hospitalized for catheter ablation. All patients underwent transthoracic and transesophageal echocardiography. According to transesophageal echocardiography, Far North patients were divided into two groups: group 1 — 21 patients with LAA thrombosis, group 2 — 141 patients without LAA thrombosis.Results. Compared to patients living in the temperate latitudes, Far North patients were younger (p=0,021) and were more likely to have type 2 diabetes (14,2% vs 8,3%, p=0,022), class ³II obesity (29,6% vs 21,1%, p=0,019), persistent AF(47,5% vs 33,2%, p=0,0019), LAA thrombosis (13% vs 6,6%, p=0,006), and severe structural and functional cardiac abnormalities (biatrial and right ventricular enlargement, lower left ventricular ejection fraction). In Far North patients, using logistic regression, independent predictors of LAA thrombosis were identified: an increase in left ventricular mass index (odds ratio (OR), 1,029; 95% confidence interval (CI), 1,011-1,048; p=0,001), persistent AF (OR, 3,521; 95% CI, 1,050-11,800; p=0,041).Conclusion. In Far North patients with nonvalvular AF, scheduled for catheter ablation, compared with patients from temperate latitudes, with a similar profile of cardiovascular diseases at a younger age, type 2 diabetes, grade ³II obesity, persistent AF, and LAA thrombosis were more common. The presence of persistent AF and an increase in left ventricular mass index are independent predictors of LAA thrombosis in Far North patients with nonvalvular AF.